The lived experience of work and city rhythms : a rhythmanalysis of London's Square Mile - Nash, Louise (Emerald Publishing Limited, 2022)
The Lived Experience of Work and City Rhythms looks at the working environment, with a focus on the geographical workplace and how this affects the experience of our working lives. It raises key questions such as: Does where we work affect our experience of work? What is the relationship between place and work? What is it like to work in a place dominated by a particular industry or sector? The book draws on empirical research carried out in the City of London - the heart of the UK's financial services sector. The 'Square Mile', as it is also known, is widely perceived to be a distinctive place because of its architecture, history, traditions, and culture. Exploring how the City is experienced as a workplace, this book also presents a method of researching such places through an attention to, and analysis of, their spatial and temporal rhythms. By illuminating how we experience the places where we work, this book explores what makes us feel that we fit in - or don't fit in - to certain places, how a sense of place endures, and how the relationship between people, place, and work can be researched.